Mobile Assisted Language Learning: Platfoms To Support Students Teacher Improving Reading Skill - Auliya, Prativi Khilyatul; Ardiyansah, Tri Yuli; Muhammad, Ribeh Najib (Jetlal, 2021)
This study was investigating the platforms on Mobile Assisted Language Learning (MALL) that mostly used by students teachers on first and second year to improve their reading skill. Qualitative research design which used questionnaire and interview was employed to gain and analyze the data. The result showed that 79.3% students benefited various platforms, while the rest never used any platforms to support improving their reading skill. The top-five platforms were; (1) Wattpad, (2) Social Media, (3) Duolingo, (4) U-Dictionary, and (5) Quora. Students favored those platforms due to its popularity, attractiveness, efficiency, and benefit. The up-to-date and popular platform such as various social media and Quora were used to improve reading skill by connecting them to communicate to English native. Attractive platform such as Wattpad, where they could read countless stories was demanded to please their soul of readers. The efficient ones, Duolingo and U-Dictionary were chosen by them who prefer to learn in organized way. Fortunately, all of those platforms offered advantages for students such as improving their vocabulary acquisition, grammar competence, reading speed, and reading comprehension as well.